On English Translation of Public Signs in Scenic Spots from the Perspective of Eco-translatology—Taking Sichuan Province as an Example - Liao, Chenmei (Journal of Theory and Practice in Linguistics, 2024)
Scenic spots are rapidly becoming a key instrument in external communication. To improve the translation quality of tourism signs, this article explores the translation of public signs at Sichuan tourist attractions on the basis of eco-translatology. The author concludes that scenic spots should be standardized in linguistic, cultural and communicative dimensions.